Organisational-level risk and health-promoting factors within the healthcare sector—a systematic search and review - Akerstrom, Magnus; Wahlström, Jens; Lindegård, Agneta; Arvidsson, Inger; Fagerlind Ståhl, Anna-Carin (Frontiers in Medicine, 2025)
IntroductionThe healthcare sector is globally experiencing increasing demands and workplace interventions on an organisational level is sought to create healthy workplaces. The aim of this study was to provide an overview of Nordic research on the work environment and health of healthcare professionals, with a focus on identifying organisational-level risk and health-promoting factors.MethodsThis systematic search and review was based on an analysis of studies published in peer-reviewed journals between 1 January 2016 and 3 January 2023. The selected studies investigate the relationships between organisational-level risk and health-promoting factors and measures of health and well-being among healthcare professionals during ordinary operations. To increase applicability, this systematic search and review was limited to the Nordic countries as they share the same context with a publicly-funded widely accessible healthcare system. A total of 2,677 articles were initially identified, with 95 original studies meeting the criteria for relevance and quality.ResultsIdentified organisational risk and health-promoting factors were categorised into five categories: work schedule distribution, operations design and work methods, ergonomic conditions, working conditions and personnel policies, and the organisation’s ethical environment. In addition, two themes across the categories emerged, providing further insight into the implications for practice. The first theme emphasises risk and health-promoting factors in the actions that employers take to fulfil the organisation’s goals. The second theme emphasises risk and health-promoting factors in connection with the ability of employees to do their jobs at a level of quality they deem acceptable.ConclusionSeveral organisational-level risk and health-promoting factors were identified, and the results indicate that the actions that employers take to fulfil the health-care organisation’s goals and promote the ability of employees to provide high-quality care are important for the health and wellbeing of healthcare employees.